Analisis Getaran Balok Komposit Fiberglass Dengan Variasi Tumpuan Jepit-Jepit, Jepit-Bebas, dan Jepit-Rol - Marwin, Marwin; Endriatno, Nanang; Sisworo, Raden Rinova (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2023)
Vibration is an alternating motion through its equilibrium point caused by a disturbance or deviation. This study aims to determine the value of vibrational displacement in fiberglass composite beams supported by fixed-fixed, fixed-free, and fixed-roll. The research method includes the design of a vibration test tool made of U-profile steel. The test material uses a composite beam measuring 1000 mm x 25 mm x 25 mm. variations in the placement of the exciter are 10 cm, 25 cm, 40 cm, 55 cm, and 70 cm. the result of the study were obtained on the support of the fixed-fixed the highest deviation value was at a distance of 25 cm, namely 0.193 mm, and the lowest value at a distance of 70 cm, namely 0.096 mm. On the fixed-free support the highest deflection value is at a distance of 70 cm which is 0.455 mm, and the lowest value is at a distance of 10 cm which is 0.133 mm. And while on the fixed-roll pile the highest deviation value is at a distance of 10 cm, which is 0.123 mm. Kata kunci: vibration, displacement, composite, support variation.